Magnetic Resonance Spectroscopy in Neurofibromatosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The functional significance of T2 hyperintense lesions (UBOs) and their role in learning disabilities associated with neurofibromatosis type 1 (NF-1) were studied by quantitative magnetic resonance spectroscopy (MRS) in 7 male patients, aged 6-19 years, and 7 controls, at Johns Hopkins University, Baltimore, MD.